Model Tata Kelola Strategis Destinasi Multi-Fungsi: Integrasi Nilai Sakral Keagamaan dan Kearifan Lokal di Situs Taman Purbakala Pugung Raharjo - Roliyanti, Roliyanti; Riyanto, Kuncoro Budi; Febriyanto, Febriyanto (Jayapangus Press, 2026)
The Pugung Raharjo Archaeological Park in East Lampung faces complex managerial challenges as a multi-functional destination encompassing conservation, tourism, and ritual space. This study aims to formulate a participatory strategic governance model to balance these three functions, particularly in accommodating the sacred values of megalithic remains actively used for Hindu spiritual rites. A qualitative method with a multi-stakeholder case study approach was employed. Primary data were gathered through in-depth interviews with the Cultural Heritage Preservation Office (BPK) Region VII, the East Lampung Regency Government, site guardians, and the Hindu community. Data were analyzed using the Miles and Huberman interactive method, grounded in Stakeholder Theory. The findings reveal that while no open conflicts have occurred, the current operational management of the site remains sporadic, relying on